Incidence of venous thromboembolism in rheumatoid arthritis, results from a "real-life" cohort and an appraisal of available literature. Issue 33 (20th August 2021) - Conforti, Alessandro; Berardicurti, Onorina; Pavlych, Viktoriya; Di Cola, Ilenia; Cipriani, Paola; Ruscitti, Piero
Abstract : Abstract: Rheumatoid arthritis (RA) is associated with an increased risk of venous thromboembolism (VTE) occurrence. In this work, we assessed the incidence and predictive factors of VTE in our "real-life" cohort of RA patients. To contextualize our results, we reviewed the available literature about this topic. We performed a retrospective analysis of prospectively followed-up patients with RA attending our Rheumatologic Clinic between January 2010 and December 2020. Each patient was investigated for VTE occurrence. Incident cases were reported as incidence proportion and incidence rate per 1000 person-years at risk. Possible predictive factors were also exploited by regression analyses. Available literature about this topic was also assessed. In this evaluation, 347 consecutive patients without previous evidence of VTE, attending our Rheumatologic Clinic from 2010 to 2020, were studied. In our "real-life" cohort, the incidence proportion of VTE was 3.7% (2.7–4.7%) and considering over 1654 person-years, an incidence rate of 7.8 × 1000 (2.5–11.7). Exploratively assessing predictive factors in our cohort, older age (hazard ratio [HR] 1.07, 95% confidence interval [CI] 1.01–1.14, p = .015), higher body mass index (HR 1.37, 95% CI 1.04–1.80, P = .026), and longer disease duration (HR 1.11, 95% CI 1.03–1.20, P = .006) resulted to be significant predictors of VTE occurrence during the follow-up. In our "real-life" cohort, VTE burden has been suggested in patients with RA. Comparing our results with previous data derived from randomized controlled trials and administrative data, some different findings were retrieved about incidence of VTE. Assessing predictive factors, older age, higher body mass index, and longer disease duration resulted to be significant predictors of VTE occurrence during the follow-up. Taking together these observations, a further evaluation of this issue on specific designed studies is needed to provide more generalizable results to the daily clinical practice.